1972
DOI: 10.1042/bj1280685
|View full text |Cite
|
Sign up to set email alerts
|

The osmotic properties of sulphoethyl-Sephadex. A model for cartilage

Abstract: 1. Observations are reported on the variation of the swelling of sulphoethyl-Sephadex C-50 and C-25, and of the partition of NaCl between solution and gel, with the concentration of NaCl. 2. The results were interpreted in terms of Manning's (1969) treatment of the interactions between polyionic polymers and simple electrolytes and of Flory's (1953) treatment of the swelling of gels. 3. The results indicate net inner osmotic pressures as high as 3.6x10(5)Pa (140 mosmolar=3.6x10(5)N/m(2)) in 0.15m-NaCl. 4. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Calculations, based on the results, showed that the total swelling pressure of cartilage was in the order of 0.1 MN/m^. This value was close to that obtained for bovine nasal septum and sulfoethyl-Sephadex beads by Ogston and Wells (1972), but it was lower than the value predicted by Ogston (1970). More recently Maroudas (1979) has stated that the osmotic pressure of cartilage is approximately 0.2 MN/m^.…”
Section: A ^F Ajttr^ysupporting
confidence: 63%
“…Calculations, based on the results, showed that the total swelling pressure of cartilage was in the order of 0.1 MN/m^. This value was close to that obtained for bovine nasal septum and sulfoethyl-Sephadex beads by Ogston and Wells (1972), but it was lower than the value predicted by Ogston (1970). More recently Maroudas (1979) has stated that the osmotic pressure of cartilage is approximately 0.2 MN/m^.…”
Section: A ^F Ajttr^ysupporting
confidence: 63%
“…Although the existence of charge-screening in macroions may be a revelation to many current biochemical researchers, the concept has long been recognized as being central to our understanding of the charge-related characteristics of nucleic acids 4,5 and synthetic polyelectrolytes, such as polyacrylate 21 and polymethacrylate, 1,17,[22][23][24] as well as polysaccharides. [6][7][8]17,25 May this communication help to reinforce this important aspect of the solution behavior of polyelectrolytes that is frequently overlooked in biochemistry and molecular biology textbooks.…”
Section: Discussionmentioning
confidence: 87%
“…The calculations with the charged fiber model were based on water at room temperature with ion diffusivities of D K1 ¼ D ClÀ ¼ 2:0310 À9 m 2 =s: The literature generally estimates the chondroitin sulfate charge as corresponding to one sulfate substitution and one carboxyl group per disaccharide, GAG radii as 0.5-1.0 nm, and length as 1 nm per disaccharide (corresponding to 105 nm for a 50 kDa chondroitin sulfate) (1,(24)(25)(26). The properties of GAG fibers used here were r ¼ 0.5 nm, a net charge of À2 per disaccharide, a length of 1 nm per disaccharide, and a disaccharide molecular weight of 457 Da.…”
Section: Microstructural Modelmentioning
confidence: 99%